Fair Wages and Social Welfare - Helmedag, Fritz (Journal of Income Distribution®, 2011)
Based on considerations concerning justice, average and minimum wages as well as unemployment aid are determined. The derived guidelines refer to net product and reflect `reasonable' proportions between the income categories. Thus, deviations from the suggested principles may be classified as inappropriate.